Physically and chemically gelling hydrogel formulations based on poly(ethylene glycol) diacrylate and Poloxamer 407. (13th January 2017) - Markus, Felix; Dreher, Felix; Laschat, Sabine; Baudis, Stefan; Tovar, Günter E.M.; Southan, Alexander
Abstract: Poloxamer 407 (P407) and poly (ethylene glycol) diacrylate (PEG-DA) are well-characterized building blocks for physical and chemical hydrogels, respectively. P407 physical hydrogels alone can be used as injectable hydrogels, but lack mechanical stability. In this contribution, PEG-DA was added to physically gelling P407 solutions in order to introduce chemical curing ability. The resulting hydrogel formulations containing P407, PEG-DA ( M n  = 700 g mol −1 ) and the photoinitiator 1-[4-(2-hydroxyethoxy)phenyl]-2-hydroxy-2-methyl-1-propan-1-one (Irgacure 2959) were characterized concerning their physical and chemical gelling behavior. Upon addition of PEG-DA to P407 solutions, their gel transition temperature T gel was altered and could be adjusted between 10 °C and 39 °C. At P407 concentrations c Polox of <22.5 wt.-%, T gel increased compared to P407 solutions by adding PEG-DA. At c Polox >22.5 wt.-% T gel decreased. The different behavior at different c Polox could be explained by a combination of a decrease of P407 micelle size as well as a decrease of the critical mizellization temperature of P407 upon PEG-DA addition. Chemical gelation of the formulations was investigated by real-time FT-IR spectroscopy combined with photorheology as well as by the equilibrium degree of swelling and shear moduli of the cured hydrogels. Hydrogel curing was significantly faster without altering the double bond conversion when P407 was present in the formulations, probably due to prearrangement of the double bonds. The shear moduli and equilibrium degrees of swelling of the cured hydrogels could be adjusted by the PEG-DA concentration in the formulation, similar to pure PEG-DA hydrogels. The hydrogel formulations presented are promising candidates for injectable hydrogels with chemical curing ability. Graphical abstract: Highlights: Solutions of Poloxamer 407 and poly (ethylene glycol) diacrylate were investigated. The solutions show a physical gelling in a wide concentration window. Photocuring of poly (ethylene glycol) diacrylate is accelerated by Poloxamer 407. Stiffness and water content of cured hydrogels can be adjusted.